Nursing student-patient relationship-a 10-year comparison study in Finland - Suikkala Arja; Leino-Kilpi Helena; Katajisto Jouko (De Gruyter Open Ltd, 2022)
Objective
This study aimed to describe and compare the group-level findings from 2005–2006 and 2015–2016 regarding students’ and patients’ views of the nursing student-patient relationship and associated factors.
Methods
The data were in both cases collected using Student-Patient Relationship Scales. The data were analysed statistically.
Results
In both student cohorts, authoritative and facilitative student-patient relationships were reported by the students more frequently than mechanistic relationships. Authoritative relationships were most common in both patient cohorts, whereas facilitative relationships had become more frequent than mechanistic relationships. A positive change of views in the student and patient cohorts was found in factors associated with the relationship.
Conclusion
In order to strengthen a clinical learning culture that reflects a facilitative student-patient relationship, further research is needed on the processes and outcomes of that relationship.